Familial isolated hyperparathyroidism is linked to a 1.7 Mb region on chromosome 2p13.3–14. Issue 3 (8th March 2006) - Warner, J V; Nyholt, D R; Busfield, F; Epstein, M; Burgess, J; Stranks, S; Hill, P; Perry-Keene, D; Learoyd, D; Robinson, B; Teh, B T; Prins, J B; et al.
Abstract : Bachground: Familial isolated hyperparathyroidism (FIHP) is an autosomal dominantly inherited form of primary hyperparathyroidism. Although comprising only about 1% of cases of primary hyperparathyroidism, identification and functional analysis of a causative gene for FIHP is likely to advance our understanding of parathyroid physiology and pathophysiology. Methods: A genome-wide screen of DNA from seven pedigrees with FIHP was undertaken in order to identify a region of genetic linkage with the disorder. Results: Multipoint linkage analysis identified a region of suggestive linkage (LOD score 2.68) on chromosome 2. Fine mapping with the addition of three other families revealed significant linkage adjacent to D2S2368 (maximum multipoint LOD score 3.43). Recombination events defined a 1.7 Mb region of linkage between D2S2368 and D2S358 in nine pedigrees. Sequencing of the two most likely candidate genes in this region, however, did not identify a gene for FIHP. Conclusions: We conclude that a causative gene for FIHP lies within this interval on chromosome 2. This is a major step towards eventual precise identification of a gene for FIHP, likely to be a key component in the genetic regulation of calcium homeostasis.